1997
DOI: 10.1016/s0167-8140(97)00172-2
|View full text |Cite
|
Sign up to set email alerts
|

Is pulsed dose rate more damaging to spinal cord of rats than continuous low dose rate?

Abstract: Background and. purpose: Theoretical calculations suggest that pulsed dose-rate irradiation (PDR) should have approximately the same effectiveness as continuous low dose-rate (CLDR) when the same total dose is given in the same overall time, unless large doses per pulse (> 2 Gy) are used and/or non-exponential or very short half-times of repair (<0*5 h) are present in the irradiated tissues. However, few animal experiments have been reported to test this theory, and some of them gave contradictory results. W e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Haustermans et al . [38] attempted to define a pulsed dose rate of isoeffective protocol with a continuous low dose rate irradiation of a rat cervical spinal cord. Two different schedules were used, delivering pulses of 0.69 Gy at 1 h repetition (9 pulses/day) and of 2 Gy at 3 h repetition (4 pulses/day), with overnight intervals of 12-15 h. The reference LDR exposure used a range of dose rates up to 0.94 Gy/h.…”
Section: Discussionmentioning
confidence: 99%
“…Haustermans et al . [38] attempted to define a pulsed dose rate of isoeffective protocol with a continuous low dose rate irradiation of a rat cervical spinal cord. Two different schedules were used, delivering pulses of 0.69 Gy at 1 h repetition (9 pulses/day) and of 2 Gy at 3 h repetition (4 pulses/day), with overnight intervals of 12-15 h. The reference LDR exposure used a range of dose rates up to 0.94 Gy/h.…”
Section: Discussionmentioning
confidence: 99%
“…When there are several mono-exponential components, each with different repair half times, the corresponding BED for closely spaced equation is simply the total dose multiplied by the weighted addition of the respective RE factors, 9,10 i.e. :…”
Section: Multiexponential Repairmentioning
confidence: 99%
“…Equations (8)(9)(10) all consider repair to be a mono-exponential process. This is consistent with the first-order assumption Lea and Catcheside chose to use; they did consider that an alternative (second-order) process might be more appropriate but concluded that, for their purposes, the predictive differences between the two would be insignificant.…”
Section: Protracted Exposure and The Leacatcheside Modelmentioning
confidence: 99%
“…The therapeutic ratio of PDR vs LDR depends on cycle dose size and interval and tissue repair characteristics [a/b ratios and repair half-times (T 1/2 )]. In normal tissues with a T 1/2 ,0.5-h component, PDR may be more damaging than LDR [18], but the effect should be reduced if the dose per cycle is ,1 Gy [16,19].…”
mentioning
confidence: 99%